2009
DOI: 10.1007/s10552-009-9421-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to second cancer screening practice in disease-free cervical cancer survivors

Abstract: Lack of a recommendation for second cancer screening from health care providers and the misperception of second cancer risk might have negative impacts on the breast cancer screening behaviors in cervical cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…15,37 In the current study, only 21.5% of study participants reported having received a recommendation for SPC screening, but 98% of the participants said that they would undergo cancer screening if physicians recommended it. The low screening rates in the current study may thus be in part because of a lack of physician recommendation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…15,37 In the current study, only 21.5% of study participants reported having received a recommendation for SPC screening, but 98% of the participants said that they would undergo cancer screening if physicians recommended it. The low screening rates in the current study may thus be in part because of a lack of physician recommendation.…”
Section: Discussionmentioning
confidence: 60%
“…40 Previous studies have found inconsistent associations between perceived risks and benefits and screening practices. 15,16 Although some studies have found that increased perceived vulnerability among cancer survivors resulted in increased screening, 15 Mayer et al found no association in an analysis of the 2003 US Health Information National Trends Survey (HINTS). 16 In the current study, perceived risk and screening practice were not found to be significantly associated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer survivors would have different health beliefs, including perceived risk, self-efficacy, and risk perceptions related to cancer screenings, all of which may influence screening behaviors [14]. They felt that they were at higher risk of developing another cancer compared to the general population, and they acknowledged the benefits of screening [29]. However, even for participants with a previous cancer, screening rates in our study were only 30-50%, much lower than in the United States where 70-95% of survivors had breast and cervical cancer screening and 40-85% of them had colorectal cancer screening [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients do not undergo SPC screening due to an inappropriate perception of SPC risk (Park et al, 2009), fear of cancer recurrence and a desire to avoid thinking about illness (Bober et al, 2007). Lack of knowledge and information about SPC among cancer patients are other key barriers to SPC screening (Shin et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%